PENGARUH HARGA, KERAGAMAN PRODUK DAN MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK PADA PT. INDEX SUKOHARJO - Manab Semarang; Sri Hartono; Burhanudin Ahmad Yani (JURNAL ILMIAH EDUNOMIKA, 2019)
The purpose is to know the effect off prices, product diversity and brands on product purchasing decisions at PT. Index Sukoharjo both simultan and partially. This research was conducted with a quantitative approach, collection data was done by distributing question naires and documentation. The sample used was 85 people. The analytical tool used is test data instruments, classic assumption tests and multiple linear regression. The results and have been found and proven that all research data include valid and realiable categories, so that the research data is feasible to continue in the subsequent data analysis process. The results of the hypothesis testing of this study using econometric tests in the form of multiple linear regression (multiple regression) obtained the equation: Y = - 0.587 +0.350X1 + 0.380X2 +0.315X3. Product diversity is the most dominant variable in influencing customer purchasing decisions on furniture products of PT. Index Sukoharjo. In the determination of price variables, product diversity, brands have an influence on product purchasing decisions by 66%. PT. Index needs to look for other factors that may also increase customer purchasing decisions on the furniture products offered. Based on the results of data analysis it is known that together and individually the price variable, product diversity, discipline and brand have a significant effect on the customer purchasing decisions of PT. Index Sukoharjo. Keywords: Brand, Price, Product Diversity, Purchasing Decision